ANALISIS MODEL BISNIS DENGAN PENDEKATAN BUSINESS MODEL CANVAS USAHA MIE ACEH DI KOTA BANDAR LAMPUNG (STUDI KASUS PADA USAHA MIE ACEH NUSANTARA CUT MUTIA) - Septian Nur Hidayat; Damayanti Damayanti; Prasetya Nugeraha (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims to determine the analysis of business models with the approach Business Model Canvas in the Mie Aceh Nusantara Cut Mutia business during a food security crisis. This type of research is a descriptive study using a qualitative approach. Data collection techniques used, namely observation, interviews and documentation. The research results show that Key Partners owned are suppliers of coffee and spices from Aceh, distributors at Pasar Pasir Gintung, owners of business premises leases, and the local sub-district government. Key Activities the activities carried out are purchasing raw materials, ordering coffee and spices, producing aceh noodles independently, selling at business outlets, and marketing offline and online. Key Resources needed, namely physical resources, intellectual resources, human resources, and financial resources. Cost Structure consists of variable costs and fixed costs. Value Propositions what is offered is a populist price, maintained taste quality, satisfying service, effective presentation, and innovating. Customer Relationship which is woven, namely by providing maximum and satisfying service, maintaining the quality of taste of all menus, employees have a friendly nature, spatial layout adapted to populist business market segmentation. Customer Segments the targets are based on geographic segments, demographic segments, and psychographic segments. Channels done by direct and indirect. Revenue Streams obtained through selling the Mie Aceh Nusantara Cut Mutia menu for free offline and online. The impact of the Covid-19 pandemic and the food crisis affected the Mie Aceh Nusantara Cut Mutia business, but the strategy to reduce profit margins has kept this business profitable.